ENKAPSULASI NANOPARTIKEL PENTAGAMAVUNON-0 DENGAN KITOSAN VISKOSITAS RENDAH DAN VISKOSITAS SEDANG SERTA EVALUASINYA MELALUI UJI TRANSPORT OBAT SECARA INVITRO - , DIAN PURWITA SARI, Dr. rer. nat. Ronny Martien, M.Si. ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Pentagamavunon-0 (PGV-0) was derived from curcumin by molecule modification which was a preeminent product of Faculty of Pharmacy GMU and developed as a new potential analgetic-antiinflammatory agent. , it was discovered that PGV-0 had a poor bioavailability due to its low solubility. Nanoparticle encapsulation using chitosan was expected to increase PGV-0 solubility profile in order to gain the bioavailability by enhancing the transport through biological membrane. The aim of this research was to produce chitosan- PGV-0 nanoparticle using low viscous and medium viscous chitosan and to do an invitro study for determining the permeation force. method. The PGV-0 nanoparticle encapsulation using low viscous and medium viscous chitosan was carried out by the ionic gelation preparation was optimized by gradual production scale, 500 ÂµL, 15 mL, and 100 mL. Chitosan-PGV-0 nanoparticle characterization included the measurement of particle size, distribution, zeta potential, morphological shape, entrapment efficiency and entrapment stability. Chitosan-PGV-0 nanoparticle permeation force was evaluated by invitro study represented by cellular uptake and diffusion test. formula The selected were NCPL (Low Viscous Chitosan 0,05%